Soil microbiological parameters in an intercropped production system under organic management (Research, Society and Development, 2022)
The different soil management systems, such as no-tillage and conventional planting, as well as crop rotation and succession, promote changes in the soil, altering factors such as the availability of water, oxygen and substrate, directly affecting the soil microbiota. The objective was to evaluate the effects of the management of intercropping systems with the presence of the legume gliricidia, without gliricidia and native vegetation on soil microbiological attributes. An experiment was carried out under field conditions, in an area of ​​organic management of land use, cultivated with legume gliricidia, fruit trees and forest essence. The design used was in randomized blocks, in which ten soil samples were collected in triplicate at two depths (0-10 and 10-20 cm). The samples were homogenized and sieved in sieves, placed in properly identified plastic bags and subsequent analysis of the microbial attributes (microbial biomass carbon-Cmic, microbial biomass nitrogen-Nmic, metabolic quotient-qCO2 and basal respiration (RBS). that the cultivation systems caused significant alterations in the microbiological attributes of the soil when compared with the native vegetation. of the native vegetation, while the values ​​of Cmic, RBS and qCO2 did not differentiate.These results confirm that the intercropping systems with the presence of gliricidia was equal to the native forest, in providing favorable conditions for the mineralization of organic matter by the soil microbiota.